Identification of liver‐derived bone morphogenetic protein (BMP)‐9 as a potential new candidate for treatment of colorectal cancer. Issue 2 (28th November 2021) - Cai, Chen; Itzel, Timo; Gaitantzi, Haristi; de la Torre, Carolina; Birgin, Emrullah; Betge, Johannes; Gretz, Norbert; Teufel, Andreas; Rahbari, Nuh N.; Ebert, Matthias P.; Breitkopf‐Heinlein, Katja
Abstract: Colorectal cancer (CRC) is a high‐incidence malignancy worldwide which still needs better therapy options. Therefore, the aim of the present study was to investigate the responses of normal or malignant human intestinal epithelium to bone morphogenetic protein (BMP)‐9 and to find out whether the application of BMP‐9 to patients with CRC or the enhancement of its synthesis in the liver could be useful strategies for new therapy approaches. In silico analyses of CRC patient cohorts (TCGA database) revealed that high expression of the BMP‐target gene ID1, especially in combination with low expression of the BMP‐inhibitor noggin, is significantly associated with better patient survival. Organoid lines were generated from human biopsies of colon cancer (T‐Orgs) and corresponding non‐malignant areas (N‐Orgs) of three patients. The N‐Orgs represented tumours belonging to three different consensus molecular subtypes (CMS) of CRC. Overall, BMP‐9 stimulation of organoids promoted an enrichment of tumour‐suppressive gene expression signatures, whereas the stimulation with noggin had the opposite effects. Furthermore, treatment of organoids with BMP‐9 induced ID1 expression (independently of high noggin levels), while treatment with noggin reduced ID1. In summary, our data identify the ratio between ID1 and noggin as a new prognostic value for CRC patient outcome. We further show that by inducing ID1, BMP‐9 enhances this ratio, even in the presence of noggin. Thus, BMP‐9 is identified as a novel target for the development of improved anti‐cancer therapies of patients with CRC.